Metal–organic frameworks as selectivity regulators for hydrogenation reactions - Zhao, Meiting; Yuan, Kuo; Wang, Yun; Li, Guodong; Guo, Jun; Gu, Lin; Hu, Wenping; Zhao, Huijun; Tang, Zhiyong (Nature (London), 2016)
The flavouring, perfume and pharmaceutical industries rely on the selective hydrogenation of α,β-unsaturated aldehydes to generate unsaturated alcohols; here, a new type of highly selective catalyst is described in which platinum nanoparticles are sandwiched between a core and a shell of a metal−organic framework. Sandwich course for catalysts Unsaturated alcohols, widely used in the flavouring, perfume and pharmaceutical industries, are produced by selectively hydrogenating C–O groups over C–C groups present in suitable starting aldehyde molecules. Developing efficient catalysts for this transformation is challenging. Here Zhiyong Tang and colleagues describe a new type of highly selective catalyst in which platinum nanoparticles are sandwiched between a core and a shell of a metal–organic framework. This arrangement results in stable catalysts that selectively hydrogenate C–O groups to produce a range of value-added unsaturated alcohols. The design strategy underpinning the work should be applicable to other selective catalysts for important yet challenging chemical reactions. Owing to the limited availability of natural sources, the widespread demand of the flavouring, perfume and pharmaceutical industries for unsaturated alcohols is met by producing them from α,β-unsaturated aldehydes, through the selective hydrogenation of the carbon–oxygen group (in preference to the carbon–carbon group) 1 . However, developing effective catalysts for this transformation is challenging 2 , 3 , 4 , 5 , 6 , 7 , because hydrogenation of the carbon–carbon group is thermodynamically favoured 8 . This difficulty is particularly relevant for one major category of heterogeneous catalyst: metal nanoparticles supported on metal oxides. These systems are generally incapable of significantly enhancing the selectivity towards thermodynamically unfavoured reactions, because only the edges of nanoparticles that are in direct contact with the metal-oxide support possess selective catalytic properties; most of the exposed nanoparticle surfaces do not 9 , 10 , 11 , 12 , 13 , 14 . This has inspired the use of metal–organic frameworks (MOFs) to encapsulate metal nanoparticles within their layers or inside their channels, to influence the activity of the entire nanoparticle surface while maintaining efficient reactant and product transport owing to the porous nature of the material 15 , 16 , 17 , 18 . Here we show that MOFs can also serve as effective selectivity regulators for the hydrogenation of α,β-unsaturated aldehydes. Sandwiching platinum nanoparticles between an inner core and an outer shell composed of an MOF with metal nodes of Fe 3+ , Cr 3+ or both (known as MIL-101; refs 19 , 20 , 21 ) results in stable catalysts that convert a range of α,β-unsaturated aldehydes with high efficiency and with significantly enhanced selectivity towards unsaturated alcohols. Calculations reveal that preferential interaction of MOF metal sites with the carbon–oxygen rather than the carbon–carbon group renders hydrogenation of the former by the embedded platinum nanoparticles a thermodynamically favoured reaction. We anticipate that our basic design strategy will allow the development of other selective heterogeneous catalysts for important yet challenging transformations.